Model Course Review Horay Berbantu Media Kartu Berpadu Permainan Tic Tac Toe dalam Pembelajarn PAI Masa PPKM - Sulfemi, Wahyu Bagja; Arsyad, Arsyad; Nurlelasari, Ela (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2022)
This study aims to increase the motivation, interest, and learning outcomes of Class IV students at SDIT Al-Hamidiyah Depok City Islamic Studies subject by showing honest, disciplined, responsible, polite, caring, and confident behavior in interacting with family, friends, teachers, and the stairs. Starting from the low learning of the KKM 70 obtained an average class of 57.14. In the second cycle of learning by using the Course Review Horay Learning Model with Card Games, an average of 90 classes was obtained, students who completed based on the learning outcomes were 18 out of 21 students or 90.48%. The results of the teacher's observations who could answer questions correctly reached 20 children or 95.24%. Using this learning model, students have motivation, interest, and are diligent in dealing with various tasks or questions given by the teacher, and can create a more lively, and fun classroom atmosphere, but stick with the Health Program in avoiding the spread of Covid 19. no learning loss due to online during the pandemic 19.